Identifying the location of recombination from voltage-dependent quantum efficiency measurements. (September 2017) - Min, Byungsul; Kruse, Christian; Schinke, Carsten; Wolf, Martin; Müller, Matthias; Sträter, Hendrik; Wagner, Matthias; Bothe, Karsten; Brendel, Rolf
Abstract: This paper investigates process-induced variations of the open-circuit voltage ( V oc ) using voltage-dependent quantum efficiency measurements. By means of device modelling we show that this method is able to explain the V oc difference of two solar cells, even if they show identical electrical behaviour under short-circuit condition. This paper furthermore explains how the origin of V oc variations can be classified into emitter, base and rear of the solar cell. The simulation results have been experimentally verified with industrial-type passivated emitter and rear cells (PERC) cells made from p-type Czochralski wafers. The proposed analysis method is an attractive way for monitoring V oc variations of solar cells in industrial mass production since there is no need for specially prepared test structures.